Pemikiran Qasim Amin Tentang Pembebasan Kaum Wanita - Jatmiko, Jatmiko (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2019)
This paper tried to describe modern Islamic thought from one of the renewal of Egypt viz Qasim Amin about "Tahrir Al-Mar'ah" or called by the liberation of women from the bondage of Egypt's society. At that time women considered one eye by Egypt's society, even though half the population there is a woman. The world of education is simply not perceived by the women at that time, because in view of Egypt's society that women The Western Stream and will still struggled in the House alone. Even on the other hand the women couldn't get anything in terms of choosing a partner or spouse. Thus, Qasim Amin gives an idea-a brilliant idea, especially for women in Egypt, let them be shows potential, talent and so on, in order to educate his children with science.